2007
DOI: 10.3168/jds.2006-190
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Ecology of Wooden Shelves Used in Ripening the French Raw Milk Smear Cheese Reblochon de Savoie

Abstract: Little work has been carried out on the microbiology of wooden shelves supporting cheese during ripening, and the safety of their use during cheese ripening has frequently been asked. Microbial characterization (enumerations on specific growth media) and description of their physicochemical conditions (pH, water activity, and salt concentration) were determined on 50 wooden shelves of 3 different ages at the end of the cheese-ripening process, using cheeses from 8 farm producers. The experiments were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 22 publications
4
49
1
3
Order By: Relevance
“…Recently, it has been demonstrated that the wooden surfaces of the vats used for the production of Ragusano PDO cheese are contaminated by microorganisms, in particular LAB, with concentrations varying between 10 3 and 10 6 CFU per square centimeter (Licitra et al, 2007;Lortal et al, 2009). Although other equipment, such as wooden shelves used for ripening, maybe the source of living microorganisms (Mariani et al, 2007), the equipment playing a key role during cheese production is undoubtedly the vat hosting milk. For this reason, in the present work the internal surfaces of the wooden vat were analyzed for the same microbial groups counted for milk, curd and whey samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the wooden surfaces of the vats used for the production of Ragusano PDO cheese are contaminated by microorganisms, in particular LAB, with concentrations varying between 10 3 and 10 6 CFU per square centimeter (Licitra et al, 2007;Lortal et al, 2009). Although other equipment, such as wooden shelves used for ripening, maybe the source of living microorganisms (Mariani et al, 2007), the equipment playing a key role during cheese production is undoubtedly the vat hosting milk. For this reason, in the present work the internal surfaces of the wooden vat were analyzed for the same microbial groups counted for milk, curd and whey samples.…”
Section: Discussionmentioning
confidence: 99%
“…In modern cheese production facilities, biofilms of psychrotrophic bacteria (3,4) and nonstarter lactic acid bacteria (5)(6)(7)(8) can form on equipment surfaces, acting as a source of contamination in successive batches of cheese. Wooden processing surfaces, including aging boards (9,10) and milk vats (11)(12)(13), are also rich sources of microbes that are important for cheese acidification and ripening. In traditional cheesemaking facilities, adventitious microbes inhabiting such equipment surfaces can represent a "house" microbiota important for the development of specific cheese characteristics (14).…”
mentioning
confidence: 99%
“…However, little work has been carried out to identify the microorganisms present. In a recent study, Mariani et al (2007) identified micrococci-corynebacteria, yeasts and moulds as dominant microflora on the shelves used in ripening the French raw milk smear cheese Reblochon de Savoie at the end of the cheese-ripening process. Since safety of their use has frequently been asked, the influence of the presence of the native multi-species biofilm present on wooden shelves on the behaviour of two Listeria monocytogenes strains was analysed: an inhibitory effect of their growth was observed only on wooden ripening shelves colonised by living native biofilms (Mariani et al, in press).…”
Section: Introductionmentioning
confidence: 98%